Mechanical properties of laser beam welded similar and dissimilar aluminum alloys. (October 2017) - Enz, J.; Kumar, M.; Riekehr, S.; Ventzke, V.; Huber, N.; Kashaev, N.
Graphical abstract: Highlights: Laser weldability of TWB's with a hard-to-weld Al-Zn-Mg-Cu alloy was achieved. Either a vanadium filler material or a large beam diameter was used. Defect-free weld seams were obtained. Formability of up to 55% of the BM was obtained for welded dissimilar joints. By PWHT and surface milling the mechanical properties could be improved. Abstract: Two approaches were used for laser beam welding of similar and dissimilar joints of AA7075 and AA5182 that aim to overcome the weldability problems of high-strength Al-Zn-Mg-Cu alloys. The first approach implies the use of vanadium foil as additional filler material, while the second implies the use of a fiber laser with a large beam diameter and a top-hat beam profile. Although both approaches result in an improved weld quality, in terms of weld appearance, porosity and cracking, the resulting mechanical properties differ considerably. The addition of vanadium leads to a local increase of microhardness in the fusion zone. However, the tensile strength of these joints is lower as for fiber laser welded joints. In direct comparison fiber laser welded joints exhibit also higher formability as the joints welded with vanadium foil. The highest formability is obtained for dissimilar joints with the medium-strength Al-Mg alloy. Due to the unavoidable softening in the weld zone of heat treatable aluminum alloys, the formability of the joints is inferior in comparison to the base materials. In addition, the positive effect of post-weld heat treatment, surface milling and warm forming on the resulting mechanical properties of similar and dissimilar joints is discussed.